Impact of synbiotics on gut microbiota during early life: a randomized, double-blind study - Phavichitr, Nopaorn; Wang, Shugui; Chomto, Sirinuch; Tantibhaedhyangkul, Ruangvith; Kakourou, Alexia; Intarakhao, Sukkrawan; Jongpiputvanich, Sungkom; Roeselers, Guus; Knol, Jan (Scientific reports, 2021)
Human milk is considered the optimal nutrition for infants and found to contain significant numbers of viable bacteria. The aim of the study was to assess the effects of a specific synbiotic combination at doses closer to the bacterial cells present in human milk, on intestinal bifidobacteria proportions (relative abundance), reduction of potential pathogens and gut physiological conditions. A clinical study was conducted in 290 healthy infants aged from 6 to 19 weeks. Infants received either a control infant formula or one of the two investigational infant formulas (control formula with 0.8 g/100 ml scGOS/lcFOS and Bifidobacterium breve M-16V at either 1 × 10 4 cfu/ml or 1 × 10 6 cfu/ml). Exclusively breastfed infants were included as a reference. Analyses were performed on intention-to-treat groups and all-subjects-treated groups. After 6 weeks of intervention, the synbiotics at two different doses significantly increased the bifidobacteria proportions in healthy infants. The synbiotic supplementation also decreased the prevalence (infants with detectable levels) and the abundance of C. difficile . Closer to the levels in the breastfed reference group, fecal pH was significantly lower while l -lactate concentrations and acetate proportions were significantly higher in the synbiotic groups. All formulas were well tolerated and all groups showed a comparable safety profile based on the number and severity of adverse events and growth. In healthy infants, supplementation of infant-type bifidobacterial strain B. breve M-16V, at a dose close to bacterial numbers found in human milk, with scGOS/lcFOS (9:1) created a gut environment closer to the breastfed reference group. This specific synbiotic mixture may also support gut microbiota resilience during early life. Clinical Trial Registration This clinical study named Color Synbiotics Study, was registered in ClinicalTrials.gov on 18 March 2013. Registration number is NCT01813175. https://clinicaltrials.gov/ct2/show/NCT01813175 .